The effect of funding liquidity regulation and ESG promotion on market liquidity - Judit Hevér; Péter Csóka (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2023)
Liquidity is a key consideration in financial markets, especially in times of financial crises. For this reason, regulatory attention to and measures in this field have been on the rise for the past years. Based on practical experience, regulations aiming at ensuring funding liquidity or, in general, reducing certain risky positions have the side effect of reducing market liquidity. To understand this effect, we extend a standard general equilibrium model with transaction costs of trading, endogenous market liquidity, and the modeling of regulation. We prove that funding liquidity regulation or divesting bad ESG assets reduces market liquidity.
Keywords: G11; 330; market liquidity; funding liquidity; general equilibrium model; regulatory requirement; ESG related assets